Variable impact of compost on phosphorus dynamics in organic dryland soils following a one‐time application. Issue 4 (15th June 2021) - Atoloye, Idowu A.; Jacobson, Astrid; Creech, Earl; Reeve, Jennifer
Abstract: Prolonged benefits following a single application of compost in organic dryland wheat ( Triticum aestivum L.) in the western United States have been documented, including the long‐term bioavailability of phosphorus (P). Information on the bioavailability and forms of P following a one‐time compost application in marginal organic agroecosystems with low and infrequent use of fertilizers is required to promote sustainability. The goal of this study was to evaluate changes in Hedley P pools following a one‐time application of manure compost and its potential influence on short‐term (3‐yr) P bioavailability. Steer manure compost at 0, 25, and 50 Mg dry weight ha –1 was applied to two organic dryland sites, Snowville and Blue Creek, with contrasting soil characteristics in northern Utah in a randomized complete block design. Potential phosphatase assays, a laboratory aerobic incubation study, and soil P fractionations were carried out to assess the transformation of P 1 and 3 yr after a one‐time compost application. At 0–10 cm, compost application resulted in increased acid phosphatase at Snowville (67.3 vs. 42.7 μg p‐nitrophenol g –1 soil, p = .003), while alkaline phosphatase increased at Blue Creek (124 vs. 49 μg p‐nitrophenol g –1 soil, p = .0185). The path coefficient between compost P and Hedley labile inorganic P was significant at Snowville, but not at Blue Creek, suggesting that the pathways of P differed between the sites. The Hedley stable P pool was a sink of compost P at Snowville but a source at Blue Creek. In conclusion, our work shows that a one‐time compost application had a differential effect on the variation in P dynamics in organic dryland winter wheat–fallow soils. The potential long‐term benefits may be greater in semiarid soils with lower available P levels, higher carbonate levels and pH, and drier conditions. Core Ideas: We studied the impact of a one‐time compost on soil P transformation after 1 and 3 yr. Differences in microbial activity at the two sites affected P distribution. The one‐time compost had a differential impact on P pools at the two sites. Residual effect of compost on Hedley stable P pool was greater under higher CaCO3 levels.